Promoting economic cooperation in South Asia beyond SAFTA - Ahmed, Sadiq; Kelegama, Saman; Ghani, Ejaz.; Sage eBooks (Thousand Oaks, Calif. ; London. : SAGE, 2010)
This volume examines the dichotomy between the two faces of South Asia - one poverty stricken and lagging in development, the other highly urbanized and growing rapidly - and tries to find a workable solution to bridge this gap. It looks at the many policy and institutional constraints that contribute to this dichotomy, especially regional conflict that has made South Asia one of the least integrated regions of the world.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: South Asia -- Foreign economic relations; South Asia -- Economic policy; South Asia -- Economic integration; Electronic books